Proses Penuaan (Aging) pada Paduan Aluminium AA 333 Hasil Proses Sand Casting - Anne Zulfia; Ratna Juwita; Ari Uliana; I Nyoman Jujur; Jarot Raharjo (Institute of Research and Community Outreach, Petra Christian University, 2010)
The use of aluminum alloys AA 333 as automotive component is progressively expand with the expanding desire to lose weight from the used component. However, the as-cast product from aluminum alloys AA 333 is still having low mechanical properties, so it needs the other process to increase the hardness value; one of the processes is through heat treatment process. The heat treatment process for this materials is T6 process (artificial aging), including: solution treatment at temperature 525 oC for 8 hour, quenching and various time of aging process. Aging was conducted at 180 oC for 25 minutes, 1 hours, 5 hours, 8 hours and 16 hours respectively. For aging 5 hours, the aging temperature was applied various from 110 oC, 150 oC, 180 oC, 200 oC to 250 oC, so the expected result from this research is to know the influence of the variation to morphological change of microstructure and hardness value of aluminum alloys AA 333. The results had indicated that the aging process at 180 oC caused the increased of the hardness value of each phases: α-Al matrix, primary silicon, eutectic Al-Al2Cu and Al15 (Fe, Mn)3Si2 and also caused the increased of the hardness value of aluminum alloys AA 333, from the condition of as-cast, as-quench, aging process for 25 minutes, 1 hours, 5 hours, 8 hours and 16 hours. And others results had indicated that the aging process for 5 hours also caused increasing of hardness value of each phases. The aging process (at 180 oC) for 8 hours and 5 hours) represented the most optimum time to obtained the best combination from phase distribution, that spread over in the rich matrix of aluminum and the size measured from each phase, therefore giving the highest hardness value. Abstract in Bahasa Indonesia: Penggunaan paduan aluminium AA 333 sebagai komponen otomotif semakin berkembang bersamaan dengan semakin berkembangnya keinginan untuk mengurangi berat dari komponen yang digunakan. Namun paduan aluminium AA 333 as-cast masih memiliki sifat mekanis yang rendah sehingga diperlukan proses lain untuk meningkatkan kekerasannya, salah satunya melalui proses perlakuan panas. Proses perlakuan panas yang dipilih dalam penelitian ini adalah proses perlakuan panas T6 (artificial aging), yang meliputi tahapan: solution treatment pada temperatur 525oC selama 8 jam, quenching dan proses aging. Variabel yang digunakan dalam penelitian ini adalah variasi waktu aging (temperatur 180oC), yaitu 25 menit, 1 jam, 5 jam, 8 jam dan 16 jam dan variasi temperatur aging (waktu aging 5 jam), yaitu 110oC, 150oC, 180oC, 200oC, 250oC. Dari penelitian ini diharapkan dapat diketahui pengaruh dari variasi tersebut terhadap perubahan struktur mikro dan nilai kekerasan paduan aluminium AA 333. Hasil penelitian menunjukkan bahwa aging temperatur 180oC menyebabkan peningkatan kekerasan dari tiap fase: matrik α-Al, silikon primer, eutektik Al-Al2Cu dan Al15(Fe,Mn)3Si2 dan menyebabkan peningkatan kekerasan paduan aluminium AA 333, dari kondisi as-cast, as-quench, dan waktu aging 25 menit, 1 jam, 5 jam, 8 jam dan 16 jam. Hasil penelitian lainnya juga menunjukkan bahwa proses aging selama 5 jam juga menyebabkan peningkatan kekerasan dari tiap fase. Waktu aging (pada temperatur 180oC) selama 8 jam dan temperatur aging (selama 5 jam) pada 180oC merupakan waktu yang paling optimum untuk memperoleh kombinasi yang terbaik dari distribusi fase, yang tersebar merata dalam matrik kaya Al, dan ukuran dari masing-masing fase sehingga menghasilkan nilai kekerasan yang tertinggi. Kata kunci: Aluminium AA333, penuaan buatan (T6), kekerasan, struktur mikro.